2012
DOI: 10.1377/hlthaff.2011.0819
|View full text |Cite
|
Sign up to set email alerts
|

Ten Modifiable Health Risk Factors Are Linked To More Than One-Fifth Of Employer-Employee Health Care Spending

Abstract: An underlying premise of the Affordable Care Act provisions that encourage employers to adopt health promotion programs is an association between workers' modifiable health risks and increased health care costs. Employers, consultants, and vendors have cited riskcost estimates developed in the 1990s and wondered whether they still hold true. Examining ten of these common health risk factors in a working population, we found that similar relationships between such risks and total medical costs documented in a w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
120
1
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 153 publications
(131 citation statements)
references
References 23 publications
2
120
1
2
Order By: Relevance
“…This study adds to the body of knowledge regarding the association of long-term shiftwork with sickness absenteeism among high-stress occupations and may have future implications that ultimately lead to interventions that could improve shiftworkers' health and also alleviate the economic burden associated with sick leave absenteeism (Merkus et al, 2012). For example, obese workers cost 27.4% higher in health care costs (Goetzel et al, 2012). A recent study (Zimmerman, 2012) indicates that workplace programs to promote the health and fitness of police officers can be an effective means for reducing cardiovascular risk but are commonly lacking despite the fact that currently employed police personnel have a high prevalence of traditional risk factors for CVD and obesity may be more common in police officers compared with other groups.…”
Section: Discussionmentioning
confidence: 88%
“…This study adds to the body of knowledge regarding the association of long-term shiftwork with sickness absenteeism among high-stress occupations and may have future implications that ultimately lead to interventions that could improve shiftworkers' health and also alleviate the economic burden associated with sick leave absenteeism (Merkus et al, 2012). For example, obese workers cost 27.4% higher in health care costs (Goetzel et al, 2012). A recent study (Zimmerman, 2012) indicates that workplace programs to promote the health and fitness of police officers can be an effective means for reducing cardiovascular risk but are commonly lacking despite the fact that currently employed police personnel have a high prevalence of traditional risk factors for CVD and obesity may be more common in police officers compared with other groups.…”
Section: Discussionmentioning
confidence: 88%
“…It is well documented that a large proportion of diseases and disorders are preventable. Modifiable health risk factors are precursors to a variety of diseases, disorders and premature death and are associated with increased health care costs (Goetzel et al, 2012). 6 There is further evidence that modifiable health risks can be improved through workplace financed health promotion and disease prevention programs and that improvement in health risks of a company's workforce can lead to reductions in health costs.…”
Section: Why Should a Business Invest In Health Promotion And Diseasementioning
confidence: 99%
“…Our counterintuitive finding that poor diet was associated with higher WHAI scores is similar to results from the HERO II study, in which poor eating habits among employees were associated with lower medical spending. 21 We hypothesize that our results and those of the HERO II study reflect how dietary habits are reported by health risk assessment respondents in contrast to their actual behavior. Furthermore, health risk assessment instruments that measure diet vary greatly, and our dichotomized indicators for high risk for poor diet may obscure important nuances associated with food choices.…”
Section: Exhibitmentioning
confidence: 67%
“…It was common for employees to have the condition or other risk factors for heart disease, with the percentages of employees ranging from a low of 5.5 percent for tobacco use (which was much lower than the US adult population prevalence of 16.8 percent) 21 to a high of 71.9 percent for unhealthy weight (the same as national estimates reported by the CDC). 22 Employers reported having several programs, policies, and environmental supports for addressing cardiovascular disease and its risk factors.…”
Section: Discussionmentioning
confidence: 84%